Model-based cost-effectiveness analysis of the diagnosis and treatment of cow's milk protein allergy with amino acid-based formula compared to extensively hydrolyzed formula in Argentina - Boggio Marzet, Christian; Malagrino, Pablo; Micone, Paula; Giglio, Norberto (Frontiers in Pediatrics, 2025)
IntroductionCow's milk protein allergy (CMPA) is the most common food allergy in children under one year of age. The CMPA has a significant economic impact on health resources. The objective of this study was to estimate the cost-effectiveness of implementing a new diagnostic and treatment strategy using an amino acid-based formula in infants with suspected CMPA.Materials and methodsA simple decision tree was developed. The model simulates a cohort of Argentine children of less than 6 months with suspected CMPA who were followed with clinical checks until they were 24 months of age. The first arm considers the standard of care for diagnosis and treatment of children with suspected CMPA that suggest eliminating whole cow's milk proteins and initiating treatment with (extensively hydrolyzed formula (eHF). A diagnostic process time of 4 weeks was estimated. The second arm investigates the impact of a new diagnosis and treatment strategy that eliminates cow's milk proteins and prescribes an elementary amino acid-based formula (AAF). A period of 4 weeks was estimated to assess the diagnosis of CMPA.ResultsUsing an AAF for the diagnosis and treatment of a cohort of 12,334 children with suspected CMPA, less six month age, resulted in a saving of 3,368,176 usd and 334 months gained without symptoms,. The use of AAF, as a first line treatment, was cost saving. These results proved to be robust in the one-way sensitivity analysis.ConclusionsA diagnostic strategy using AAF offers cost savings and reduces the duration of the symptomatic period, allowing effective treatment to be established earlier, which in turn reduces direct medical expenses.